Resolving the taxonomic identities of some Dipcadi species from India - Rodrigues, Hensal Salvador; Dutta, Suchandra Ranjit; Chakral, Kiran Gangadhar (Phytotaxa, 2024)
A new variety of Dipcadi concanense is described here which shares characters of D. concanense and D. janae-shrirangii but shows more affinity towards D. concanense. Dipcadi species with pure-white flowers and brownish-black seeds characters are separated into a new series within the genus Dipcadi. Dipcadi krishnadevarayae and D. montanum var. madrasicum have been synonymised in D. montanum. Half a century-long problem about the existence and status of D. maharashtrense and D. minor has been discussed.